2020
DOI: 10.3390/nu12061673
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Antioxidant Properties of Wheat Gluten Protein Hydrolysates in Human Peripheral Blood Mononuclear Cells

Abstract: Peptides from several plant food proteins not only maintain the nutritional values of the original protein and decrease the environmental impact of animal agriculture, but also exert biological activities with significant health-beneficial effects. Wheat is the most important food grain source in the world. However, negative attention on wheat-based products has arose due to the role of gluten in celiac disease. A controlled enzymatic hydrolysis could reduce the antigenicity of wheat gluten protein hydrolysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…The antioxidant activity of protein hydrolysates may be due to several mechanisms [42], so three assays were used: decolorization of β-carotene (Figure 2a), measure of ferric reducing antioxidant power (Figure 2b) and measure of capacity to sequester the DPPH free radical (Figure 2c). BHT was always used as a positive control in all the experiments.…”
Section: Antioxidant Activity Of Chia Protein Hydrolysatesmentioning
confidence: 99%
“…The antioxidant activity of protein hydrolysates may be due to several mechanisms [42], so three assays were used: decolorization of β-carotene (Figure 2a), measure of ferric reducing antioxidant power (Figure 2b) and measure of capacity to sequester the DPPH free radical (Figure 2c). BHT was always used as a positive control in all the experiments.…”
Section: Antioxidant Activity Of Chia Protein Hydrolysatesmentioning
confidence: 99%
“…[4] Due to an increasing concern in animal welfare and the rising environmental awareness, [5] the consumption of vegetable products is becoming a common trend. In this way, a growing body of evidence has underlined several biological actions such as immune, [6,7] antioxidant [6,8] and metabolic [9][10][11] effects of different vegetable protein hydrolysates by in vitro or pre-clinical approaches. We have previously shown that Lupinus angustifolius protein hydrolysates (LPHs), generated by hydrolyzation with the commonly used food-grade endopeptidase Alcalase 2.4 L, inhibit the enzymatic activity inflammatory enzymes phospholipase A2, cyclooxygenase 2, thrombin, and transglutaminase in a cell-free system.…”
Section: Introductionmentioning
confidence: 99%
“…The average molecular weight of hydrolysates is a leading factor that determines their biological properties. Reportedly, low-MW peptides, from 2 to 20 amino acids, are more biologically active when compared to their larger parent polypeptide/proteins [ 47 ]. As depicted in Figure 2 , the protein molecular profile of KPHs showed that the peptide size was around 3.11–0.16 kDa (peaks d and e).…”
Section: Resultsmentioning
confidence: 99%